Caught in the Middle: Defensive Responses to IAT Feedback Among Whites, Blacks, and Biracial Black/Whites. (May 2015) - Howell, Jennifer L.; Gaither, Sarah E.; Ratliff, Kate A.
This study used archival data to examine how White, Black, and biracial Black/White people respond to implicit attitude feedback suggesting that they harbor racial bias that does not align with their self-reported attitudes. The results suggested that people are generally defensive in response to feedback indicating that their implicit attitudes differ from their explicit attitudes. Among monoracial White and Black individuals, this effect was particularly strong when they learned that they were implicitly more pro-White than they indicated explicitly. By contrast, biracial Black/White individuals were defensive about large discrepancies in either direction (more pro-Black or more pro-White implicit attitudes). These results pinpoint one distinct difference between monoracial and biracial populations and pave the way for future research to further explore how monoracial majority, minority, and biracial populations compare in other types of attitudes and responses to personal feedback.